Indications of free drawing through adolescent drawings - Lamari, Noudjoud (Journal of Human Sciences, 2022)
Most researchers have unanimously agreed that drawing is a behavior that is unique to humans, drawing does not mean that it is accomplished by hand movements alone, but it is the desire to leave traces on the area of ​​the paper, this desire adds to the kinetic action, the symbolic dimension of the drawing, so to draw the child, he must pass from the position of the desire to the position of the action. The mental representation that he creates before drawing is what leads him to implement and realize his drawing, and without it it is impossible to achieve it. The drawings of the adolescent are sometimes also simple and spontaneous, in which the researcher finds an infinite number of facts and connotations that help him to understand the psychology of this adolescent, his characteristics, his conflicts and his needs.